Evaluation of meibomian glands after corneal laser refractive surgeries using infrared meibography - Moataz F. Al-sawy; Ahmed M. Attallah; Ahmed I. Basiony (Delta Journal of Ophthalmology)
Background Reduced supply of functional lipids to the tear film is the outcome of meibomian gland dysfunction, which is caused by either gland blockage or inflammation. Meibomian gland (MG) atrophy is correlated with the ocular surface disease index (OSDI) and can be used as an index to evaluate the general health of the MGs. Dry eye disease frequently affects the outcome of refractive surgery, even though the latter is generally successful. Objective The aim of this study was to assess the MG alterations as a major contributor to dry eye disease following corneal refractive surgery using infrared meibography. Patients and methods This is a prospective case series study that included 50 eyes of 25 patients who were selected from the Ophthalmology Department of Menoufia University Hospital, Menoufia, Egypt from May 2023 to April 2024 and for whom bilateral corneal refractive surgery was performed. They were divided into two groups: 15 patients who were subjected to laser-assisted in-situ keratomileusis (LASIK) and 10 patients who were subjected to photorefractive keratectomy (PRK). The OSDI, noninvasive breakup time (NI BUT), and lipid layer were measured using the Mediworks dry eye diagnostic system before and 3 months after surgery. Results There was no statistically significant difference between the LASIK and PRK groups regarding the baseline NI BUT, gland loss, and OSDI (P>0.05). Three months postoperatively, the NI BUT and lipid layer grading were significantly higher among the PRK group (13.11±1.231 s and 3.89±0.323, respectively) than in the LASIK group (11.86±1.693 s and 3.37±0.568, respectively, P<0.05). On the other hand, the gland loss and OSDI were significantly lower among the PRK group (28.722±9.348% and 15.667±6.878, respectively) than in the LASIK group (33.056±11.303% and 24.977±9.223, respectively, P=0.009 and P<0.001, respectively). The mean changes after surgery of NI BUT, gland loss, lipid layer, and OSDI were significantly higher among the LASIK group than the PRK group (4.03±3.43 vs. 3.45±1.57 s, 13.40±5.80 vs. 5.40±4.41%, 0.53±0.57 vs. 0.125±0.342, and 10.10±7.91 vs. 1.80±0.22, respectively). Conclusion Gland loss and OSDI were significantly lower among the PRK group than in the LASIK group. Subsequently, the postoperative dry eye had a higher prevalence following LASIK than PRK procedure and can significantly impact the patients’ quality of life.